Acute and Subacute Toxicity Study of the Ethanolic Extract From Calotropis Gigantea R. BR. in Rodents - AJAY KSHIRSAGAR; PURNIMA ASHOK; KAUSHIK NARGOLKAR; AMOL BHANDARE; ANURAG DODAL; TANMAY DODAL (International Journal of Pharma and Bio Sciences, 2010)
Acute and subacute toxicity of the ethanolic extract from Calotropis gigantea R.Br. flower was investigated. In acute toxicity study oral dose of 2000 mg/kg of the ethanolic extract did not produce mortality or changes in the general behavior and gross appearance of internal organs of mice and rats. In subacute toxicity study, ethanolic extract was evaluated at 250, 500 or 1000 mg/kg/day, orally for 30 days in rats. The behavioral response profile of the treated mice and rat was also evaluated along with other parameters such as, absolute and relative body weight along with relative weight of various organs. Biochemical and hematological parameters were analyzed in order to study the time-dependent effect and correlation of the extract. All treated animals did not show any signs of toxicity during the experimental period. There were no significant differences in the body and organ weights between the control and the treated group of mice and rats. Hematological (WBC, RBC, HGB, HCT, MCV, MCH, MCHC, PLT, LYM and NEUT) and biochemical parameters (AST, ALT, ALP, ALBN, TB, TP, TG, BUN, creatinine and glucose) revealed either no or less alteration in the treated group. Hence, the C. gigantea was found to be safe in single dose acute and repetitive dose subacute toxicity studies.